Cyclic formation of boron suboxide crystallites into star-shaped nanoplates. (1st April 2015) - Xie, Sky Shumao; Chen, Hu; Solodkyi, Ievgen; Vasylkiv, Oleg; Tok, Alfred I.Y.
Abstract : Star-shaped boron suboxide (B6 O) nanoplates were formed through a liquid-phase reaction of amorphous boron and boron oxide. The formation of the five-vertex B6 O crystal is attributed to the oxygen-deficient state of B6 O x, where x < 1, which correlates to the lattice parameters. The mechanical properties of spark plasma sintered B6 O show a hardness of 34.8 GPa and a fracture toughness of 4.0 MPa.m 1/2 . The understanding of the relationship between crystal atomic structure and crystal morphology could be employed in the design of other boron-rich compounds.